Metalophilic lipase from Ralstonia solanacearum: Gene cloning, expression, and biochemical characterization. (January 2018) - Moayad, Waznah; Zha, Genhan; Yan, Yunjun
Abstract: A screening for lipase was carried out in the metalophile of Ralstonia solanacearum . The putative lipase gene (FW376093) was cloned and expressed using E. coli as host. Subsequently, the recombined enzyme was purified and its enzyme properties were further examined. The results indicated the lipase of FW376093 was able to catalyze hydrolysis of short-chain p-nitrophenyl esters (C2–C12). It showed the optimal temperature and pH were respectively 80 °C and 8.5. The enzyme could be significantly enhanced by Na +2, Ca +2, and Fe +2, but significantly repressed by Cu +2, Ni +2 and Mn +2 . Nevertheless, the lipase of FW376093 exhibited high tolerance to detergents and organic solvents. Phylogenetic assay reveals that it belongs to family II. The unique properties of the lipase of FW376093, having metalophilicity and high tolerance to organic solvent, render it with prosperous prospect in practical applications.